Pharmacological and Cellular Significance of Triazole-Surrogated Compounds - Verma, Naimish K.; Mondal, Dhananjoy; Bera, Smritilekha (Current Organic Chemistry, 2019)
Heterocyclic compounds have been at the hierarchy position in academia, and industrial arena, particularly the compounds containing triazole-core are found to be potent with a broad range of biological activities. The resistance of triazole ring towards chemical (acid and base) hydrolysis, oxidative and reductive reaction conditions, metabolic degradation and its higher aromatic stabilization energy makes it a better heterocyclic core as therapeutic agents. These triazole-linked compounds are used for clinical purposes for antifungal, anti-mycobacterium, anticancer, anti-migraine and antidepressant drugs. Triazole scaffolds are also found to act as a spacer for the sake of covalent attachment of the high molecular weight bio-macromolecules with an experimental building blocks to explore structure-function relationships. Herein, several methods and strategies for the synthesis of compounds with 1,2,3-triazole moiety exploring Hüisgen, Meldal and Sharpless 1,3-dipolar cycloaddition reaction between azide and alkyne derivatives have been deliberated for a series of representative compounds. Moreover, this review article highlights in-depth applications of the [3+2]-cycloaddition reaction for the advances of triazole-containing antibacterial as well as metabolic labelling agents for the in vitro and in vivo studies on cellular level.
Keywords: antibacterial